Perception, compliance and economic valuation of solid waste separation at source among households in Putrajaya and Melaka, Malaysia - Ogiri, Ibrahim Aishatu (2019)
As drastic policy response to curb the menace associated with increasing generation of municipal waste in Malaysia necessitated the introduction of the mandatory recycling programme termed separation at source. However, challenges still exist as participation is still not encouraging. An understanding of what will ensure the success of the programme from the perspective of the target population is very important. This study undertook a multifactorial approach aimed to assess perception towards the waste separation at source recycling programme, identify and evaluate preferences for attributes of waste separation at source facilities and examine determinants of separation at source compliance behaviours among households among households. A few methods including factor analysis, choice experiment (CE) and structural equation modelling (SEM) were used to address the objectives of this study. A total of 431 and 435 respondents were randomly selected from different housing types in Putrajaya and Melaka respectively. The results of the factor analysis identified two dimensions of perception (fairness and effectiveness) which were used to assess the perception of the households towards the recycling programme. The respondents in both location of study exhibited positive perception both in terms of fairness and effectiveness of the programme. Meanwhile, CE was used to estimate the preference of the households for attributes of waste separation facilities. Beside the importance attach to the provision of multiple recycling bins, interestingly the results suggested households derive utility from increased number of waste separation. SEM was used to validate and test the model that was developed to examine important factors that can enhance compliance towards the waste separation at source recycling programme. Previous studies extensively used the TPB and NAM in waste management studied, this study introduces a new dimension by integrating the TPB and NAM with the economic deterrence model. Interestingly the results showed that even with the presence of deterrence other psycho-social factors are still important to motivate compliance to recycling programmes. The model explained approximately 64% of the variance in compliance behaviour towards waste separation at source among the respondents. The most salient factors found to influence compliance behaviour include: Attitude, Perceived severity of sanction, Environmental benefit of waste separation, Moral norms and Perceived behavioural control. The outcome of this study informs policy makers about the much-needed waste separation facilities needed to support households’ waste separation. Thus, policy-makers will be able to match household demand and affordability of supply for the facilities. To encourage participation in waste separation activities, a policy mix is needed, to include the provision of appropriate waste separation facilities and moral suasion that would appeal to the households’ environmental concern. This is important to help inculcate a waste minimisation philosophy, which would help maximise the social net benefit from recycling, minimise the negative environmental impact of mixed waste disposal, and alleviate the government challenge meeting its 22% target recycling rate by 2020.